Exclusion of calcitonin as a candidate gene for the basic defect in a family with autosomal dominant supravalvular aortic stenosis. Issue 5 (May 1988) - Bennett, C P; Burn, J; Moore, G E; Chambers, J; Williamson, R; Wilkinson, J
Abstract : Supravalvular aortic stenosis (SVAS) may occur as an isolated autosomal dominant trait or as a feature of Williams syndrome. It has been suggested that a defect in calcitonin function may play a role in Williams syndrome. We have excluded calcitonin as a candidate gene for SVAS using a gene specific probe.